The Strong Connection Between Anxiety, Stress, and Digitalization in Education - Ratsameemonthon, Chadchom; Subardjo, Ratna Yunita Setiyani; Ignacio, Charmae B.; Cariño, Ramil Edward V.; Romero, Cyril B.; Vasquez-Salcedo, Ma. Zandra Bonnine (The Indonesian Institute of Science and Technology Research, 2025)
This study explores the complex relationship between anxiety, stress, and the digitalization of education among students. The transition to online learning and the increasing reliance on digital tools have intensified the challenges students face in adapting to new educational technologies. The demands for constant connectivity, the overwhelming amount of information, and the need to navigate digital platforms contribute to heightened stress and anxiety. Additionally, the reduction in face-to-face interactions and the prevalence of social comparison on digital platforms have further exacerbated mental health issues. This review synthesizes existing research on the impacts of digital education, emphasizing the need for strategies that address students’ psychological well-being. By understanding the factors that contribute to anxiety and stress, educators can create more supportive digital learning environments, promoting both academic success and mental health.